• Join over 1.2 million students every month
• Accelerate your learning by 29%
• Unlimited access from just £6.99 per month
Page
1. 1
1
2. 2
2
3. 3
3
4. 4
4
5. 5
5
6. 6
6
7. 7
7
• Level: GCSE
• Subject: Maths
• Word count: 1600

# Number grids

Extracts from this document...

Introduction

Maths coursework

(Number grids)

This is a number grid which we have been asked to, draw a box round four number, find the product of the top left number and the bottom right number in this box, then again do the same with the top right and bottom left numbers and then calculate the difference between the products.

I will also be adding some variables to this number grid and them solving them with formulas.  The variables are going to be:

1. If I don’t use a square instead we use a rectangle (M x N)
2. If I change the length of the grid instead of it being 10 we could change it to another number.
3. If I change the step length, at the moment it is 1 I could change it to 2.

For all these variables I will be working out formulas and at the end of it I will come up with one general formula.

This is the number square we are going to work on at the moment.

12x23=276

13x22=286

286-276=10

Now let’s take another four;

81x92=7452

82x91=7462

7462-7452=10

There looks as though there is a pattern going on here the answer will always be 10.

Now I am going to choose a general position of my square, the top right will be “M”.

Mx(M+11)=M2+11M

(M+1)x(M+10)= M2+11M+10

M2+11M+10 - M2+11M=10

Middle

40

90

I have decided to work out a formula for this:

In this formula “N” will be the box size and “M” is the number of a square in the top right hand corner.

M                M+N-1

M+10N-10                M+10(N-1)+N-1

=M+10(N-1)        =M+11(N-1)

M x M+11(N-1)= M2+11(N-1)

M+10(N-1) x M+N-1 = M2+11(N-1)+10(N-1) 2

M2+11(N-1)+10(N-1) 2 - M2+11(N-1) = 10(N-1) 2

This proves that the following formula is correct and working for squared numbers.  10(N-1) 2

Now I have done this I am going to work out the formula when you use a number grid which is M x N.

This formula is simple to work out as 10(N-1) 2 is for squared numbers you can multiply this out so its 10((N-1) x (N-1)).

In this “N” is the grid size but we can change this so it is length and width instead of always being the same number.

So the formula is 10((L-1)(W-1))

To prove this…….

M                M+L-1

M+10W-10                M+10(W-1)+L-1

=M+10(W-1)

M x M+10(W-1)+(L-1)= M2+10M(W-1)+M(L-1)

M+10(W-1) x M+L-1 = M2+10M(W-1)+M(L-1)+10((L-1)(W-1))

M2+10M(W-1)+M(L-1)+10((L-1)(W-1)) - M2+10M(W-1)+M(L-1)= 10((L-1)(W-1))

So this has been proven.

Now I have decided to change the size of the rows in the grid.

Conclusion

I now want to find out a general formula which would let me work out the difference.  The formula will work out the difference even if the all the following variables are changed:

• Step size
• Changing the length of the grid.
• Any size of rectangle (M x N)

This formula will be my general formula for working out all the variables with one formula.

As before “M” will be the number in the top right.

“L” is the length

“W” is the width

“T” will be for the step size

“S” will be for the size of one column in the grid.

M                M+(TL-T)

M+S(TW-T)                M+S(TW-T)+(TL-T)

M x M+S(TW-T)+(TL-T) = M2+SM(TW-T)+M(TL-T)

M+(TL-T) x M+S(TW-T) = M2+SM(TW-T)+M(TL-T)+S((TW-T)(TL-T))

M2+SM(TW-T)+M(TL-T)+S(TW-T)(TL-T) - M2+SM(TW-T)+M(TL-T) = S((TW-T)(TL-T))

This is the general rule for working out the differences when finding the product of the top right and bottom left, and take the product of the top left and bottom right from it. The formula is for all the variables which I have been working out through out this piece of work.

S((TW-T)(TL-T))

“M” will be the number in the top right.

“L” this is the length of the box

“W” this is the width of the box

“T” will be for the step size

“S” will be for the size of one column in the grid.

This student written piece of work is one of many that can be found in our GCSE Number Stairs, Grids and Sequences section.

## Found what you're looking for?

• Start learning 29% faster today
• 150,000+ documents available
• Just £6.99 a month

Not the one? Search for your essay title...
• Join over 1.2 million students every month
• Accelerate your learning by 29%
• Unlimited access from just £6.99 per month

# Related GCSE Number Stairs, Grids and Sequences essays

1. ## Number Grids Investigation Coursework

Let the top left square in the rectangle equal a, and therefore: a a+1 a+2 a+3 a+10 a+11 a+12 a+13 So the algebraic expression for the difference between the products of opposite corners would be: (top right x bottom left) - (top left x bottom right) = (a + 3)

2. ## Maths - number grid

- s(s+55) s(s+48) +7 (s+48) - s - 55s s +48s +7s +336 - s - 55s =336 As can be seen the only trend within this part of my investigation is that all my results for each rectangle is a multiple of 12.

1. ## Maths Grids Totals

I will now get the differences for other sized rectangles: 3 x 4 22 23 24 25 32 33 34 35 42 43 44 45 25 x 42 = 1050 22 x 45 = 990 1050 - 990 = 60.

2. ## Number Grids

1 2 3 4 5 6 11 12 13 14 15 16 21 22 23 24 25 26 31 32 33 34 35 36 41 42 43 44 45 46 51 52 53 54 55 56 6 x 51 = 306 1 x 56 = 56 306 - 56 =

1. ## Investigate The Answer When The Products Of Opposite Corners on Number Grids Are Subtracted.

I have chosen 7 as the starting number in this case. 2 x 2 Grid 7 8 9 10 I have done another grid just to check. 3 x 3 Grid 13 14 15 16 17 18 19 20 21 The formula will not be the same for these.

2. ## Number Grids

I will then place these results in a table before trying to work out a general rule between all the differences using an algebraic formula. Here is the investigation for a 3 x 3 grid... 1 2 3 11 12 13 21 22 23 12 13 14 22 23 24

1. ## number grid

I am going to use an 8 X 8 grid to test to see if my formula works. d = 10(s - 1)� d = 10(8 - 1)� d = 10 x 7� d = 10 x 49 d = 490 The difference between, the product of the top left

2. ## Mathematics - Number Stairs

T = n T = n 2 T = 3n + 9 T = 3n + 10 T = 3n + 11 T = 3n + 12 T = 3n + 13 3 T = 6n + 36 T = 6n + 40 T = 6n + 44 T =

• Over 160,000 pieces
of student written work
• Annotated by
experienced teachers
• Ideas and feedback to